การพัฒนาสมรรถนะแรงงานข้ามชาติในภาคอุตสาหกรรมผู้ผลิตชิ้นส่วนยานยนต์ ในเขตพื้นที่ภาคตะวันออกของประเทศไทย - วาสประเสริฐสุข, อาณัติชัย; ศรีไสย์, สุทธนู; วิภาตะกลัศ, จินต์ (Journal of Graduate School of Commerce-Burapha Review, 2016)
การวิจัยนี้มีวัตถุประสงค์ 4 ประการคือ 1) เพื่อศึกษาสภาพและปัญหาเกี่ยวกับสมรรถนะแรงงานข้ามชาติในภาค อุตสาหกรรมผู้ผลิตชิ้นส่วนยานยนต์ในภาคตะวันออกของประเทศไทย 2) เพื่อศึกษาระดับสมรรถนะแรงงานข้ามชาติ ในภาคอุตสาหกรรมผู้ผลิตชิ้นส่วนยานยนต์ในภาคตะวันออกของประเทศไทย 3) เพื่อวิเคราะห์ปัจจัยการพัฒนาสมรรถนะ แรงงานข้ามชาติในภาคอุตสาหกรรมผู้ผลิตชิ้นส่วนยานยนต์ในภาคตะวันออกของประเทศไทย และ 4) เพื่อนำเสนอ แนวทางที่เหมาะสมต่อการพัฒนาสมรรถนะแรงงานข้ามชาติในภาคอุตสาหกรรมผู้ผลิตชิ้นส่วนยานยนต์ในภาค ตะวันออกของประเทศไทยข้อมูลจากการสัมภาษณ์เชิงลึกผู้บริหาร 21 คน และ จากแบบสอบถามหัวหน้างานหรือผู้ใกล้ชิด แรงงานข้ามชาติของภาคอุตสาหกรรมผู้ผลิตชิ้นส่วนยานยนต์ 384 คน ถูกนำมาใช้ในการวิจัย ค่าสถิติที่ใช้ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน การทดสอบค่าทีแบบ One-sample t-test และ การวิเคราะห์องค์ประกอบ ผลการวิจัย พบว่า 1) สภาพและปัญหาสมรรถนะแรงงานข้ามชาติ ด้านนโยบายการส่งเสริมการใช้แรงงานข้ามชาติ มีการเน้น 2 ประเด็น สำคัญคือ ก) การใช้แรงงานข้ามชาติที่ถูกกฎหมาย และ ข) การใช้แรงงานข้ามชาติที่ผ่านบริษัทจัดหางานโดยมีสนธิสัญญา กับประเทศต้นทาง ด้านการดำเนินงานภายในระยะเวลา 2-3 ปีข้างหน้า มีการเน้น 3 ประเด็นสำคัญคือ ก) การพัฒนา คุณภาพชีวิตแรงงานข้ามชาติ ข) การให้รัฐบาลเข้ามาช่วยดูแลในเรื่องประกันสังคมของแรงงานข้ามชาติ และ ค) การจัดโซน หมู่บ้านแรงงานข้ามชาติ ด้านปัญหาการใช้แรงงานข้ามชาติ มีการเน้น 2 ประเด็นสำคัญคือ ก) การสื่อสาร และ ข) แรงงาน ข้ามชาติไม่มีความผูกพันกับองค์การ และการพัฒนาทักษะแรงงานข้ามชาติ มีการเน้น 3 ประเด็นสำคัญคือ ก) การเพิ่ม ทักษะการทำงานส่วนบุคคล การทำงานร่วมกับผู้อื่น และการทำงานเป็นทีม ข) การสร้างความเข้าใจในวัฒนธรรมองค์การ และ ค) การพัฒนาภาษาและวิธีในการติดต่อสื่อสาร 2) ระดับสมรรถนะแรงงานข้ามชาติโดยรวมทั้ง 8 ด้านอยู่ในระดับต่ำ เมื่อเปรียบเทียบกับเกณฑ์ (60% และ P < .05) คือ การทำงานเป็นทีม การให้บริการด้วยความเต็มใจ คิดเป็นระบบ การแก้ปัญหา ความสามารถใช้ภาษาอังกฤษ ทักษะการติดต่อสื่อสาร ความละเอียดรอบคอบในการทำงาน และ สามารถ ทำงานภายใต้แรงกดดัน/จัดการกับความเร่งด่วน 3) มี 20 ประเด็นสำคัญของการพัฒนาสมรรถนะแรงงานข้ามชาติ ภาคอุตสาหกรรมผู้ผลิตชิ้นส่วนยานยนต์ และ 4) มี 8 แนวทางที่เหมาะสมถูกพัฒนาขึ้นมาเพื่อใช้ในการปรับปรุง สมรรถนะแรงงานข้ามชาติในภาคอุตสาหกรรมผู้ผลิตชิ้นส่วนยานยนต์ในเขตพื้นที่ภาคตะวันออกของประเทศไทย DEVELOPMENT OF MIGRANT WORKERS COMPETENCY IN THE INDUSTRIAL SECTORS OF AUTO-PARTS MANUFACTURERS AT THE EASTERN REGION OF THAILAND Anatchai Wasprasertsuk, Suttanu Srisai and Jin Vibhatakalasa Graduate School of Organization Development Administration, Chaopraya University 60240, Thailand The purpose of this study was fourfold: First, to examine situations and problems in terms of Migrant Workers Competency (MWC) in the Industrial Sectors (IS) of Auto-Parts Manufacturers (APM) at the Eastern Region of Thailand (ERT); Second, to study the level of the MWC in the IS of APM at the ERT; Third, to analyze developmental factors of MWC in the IS of APM at the ERT; and Fourth, to present appropriate approaches for developing the MWC in the IS of APM at the ERT. Data from 21 administrators with the in-depth interview technique and 384 MWCs’ supervisor questionnaires in 7 provinces of ERT were used in this study. These statistics were employed: frequency, percentage, means, standard deviation, one-sample t-test, and factor analysis. Research findings were as follows: 1) Situations and problems in terms of MWC, the aspect of policy concerning the use of migrant workers, 2 crucial issues were emphasized: a) Using migrant workers with formulate legislation, and b) Using the migrant workers through any authentic agencies or MOU with initiating abroad. Then, the aspect of working operation during the next 2-3 years, 3 crucial issues were emphasized: a) Development of the migrant workers’ quality of life, b) Helping from government to take care of migrant workers’ social assurance, and c) Providing migrant workers’ village zoning. Also, the problem aspect for using migrant workers, 2 crucial problems should be emphasized: a) Communication, and b) Migrant workers’ no commitment. Finally, the aspect of migrant workers’ skill development, 3 crucial issues were emphasized: a) Increasing personal skills, working with other persons and teamwork, b) Building organizational culture understanding, and c) Language and communication method; 2) The levels of all 8 MWC aspects were at the low level when comparing with the established criteria (60%) and significant at the .05 level, namely teamwork, service mind, system thinking, problem solving, english literacy, communication skills, attention to details, and dealing with urgency; 3) Twenty crucial issues were found for developing the MWC in the IS of APM at